(untitled) (Journal of the Management Sciences, 2024)
This study examined the cashless policy and the Nigerian banking sector service in the Awka metropolis. For the purpose of the study, three objectives were formed which included the effect of cashless policy components like electronic payment systems on banking services, access to financial services and financial innovations of banks in the Awka metropolis. The research adopted a survey research design and the sample size was 74 while 74 questionnaires were distributed and 69 appropriately returned forming the basis for conducting this study. The study was anchored on Technology Acceptance Model (TAM) and Modernization Theory. The researcher using the Spearman rank correlation coefficient to test the hypotheses discovered that the electronic payment system affected the banking services, financial innovation and access to financial services significantly. Thus, the study recommended that electronic payment system should further be improved to increase the service delivery among banks in Awka metropolis. The provision of electronic payment system should be encouraged further too to continuously improve financial innovations and boost financial reach in Awka metropolis, Anambra state, Nigeria.